Temporal and spatial aspects of experimental tonic pain: Understanding pain adaptation and intensification. (March 2015) - Weissman‐Fogel, I.; Dror, A.; Defrin, R.
Abstract: Background: The underlying mechanisms of adaptations to pain are unclear. In order to explore whether central or peripheral mechanisms predominate, the effects of two centrally mediated phenomena – spatial summation of pain (SSP) and transcutaneous electrical nerve stimulation (TENS) – were examined. The effect of the degree of painfulness, rather than absolute stimulation intensity, was also examined. Methods: Seventeen participants received several series of individually adjusted tonic noxious‐heat stimuli (300 s), inducing an initial perceived pain of 2 (mild pain), 4 (moderate pain) and 6 (strong pain) on a visual analogue scale (VAS). The stimuli were administered to small (2.25 cm 2 ) and large (9 cm 2 ) areas to produce SSP and also during TENS treatment, during which 12 VAS ratings were obtained. Results: Adaptation occurred during VAS‐2 stimulation and was minimal, followed by intensification during VAS‐4 stimulation, whereas VAS‐6 stimulation always induced pain intensification. TENS failed to produce analgesia and SSP did not affect adaptation but affected intensification. Stimulation temperatures affected the magnitude of adaptation and intensification within each degree of painfulness. The mathematical models that best fitted the time trend with VAS‐2 and VAS‐4 were linear, whereas a power function best fitted VAS‐6 stimulation. Conclusions: The mathematical models and the lack of effect of SSP on adaptation suggest that its dominant component is peripheral. Whereas relative painfulness determines whether pain adaptation or intensification occurs (probably a defence mechanism), absolute stimulation intensities influence the magnitude of the effect. Pain intensification is differentially affected by probe size, depending upon the occurrence of initial adaptation.